Pengukuran Kinerja Keuangan Pemerintah Kota Malang Dengan Menggunakan Analisis Rasio Keuangan - Gresensia Elisabeth Tori; Ana Sopanah S; Endah Puspitasari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
The level of measurement of the financial performance system can be said to be a far more important thing to be able to do to be able to see at the level of achieving a mission that has been carried out in a group or organization and at the level of an outcome in an action on which measurement. will be able to provide an action on motivation as well as a direction for a much more effective future. As in the results of this research, it can be seen that the level of expertise in the PDK financial work system in Malang City for the 2017-2020 period if it can be known based on an independence ratio which is still in a consultative form, which can be defined as minimal, which is due to in the system of existing roles on the part of the central government with the aim of being able to maximize the existing development system in the city of Malang, it is much better and the level of independence at the level of society to be able to build an area in paying retribution and taxation can be stated to be minimal. It is known that an effectiveness ratio in the ability of an area of ​​Malang City which can carry out a realization of regional original income in the 2017-2020 period as with a target that will be applied based on real data. It can be seen that based on an efficiency ratio and the performance system of the Malang City government in the 2017-2020 period is declared good.